Identifikasi Alternatif Pengembangan untuk Pemberdayaan Industri Kecil Hasil Peternakan Potensial di Kabupaten Bogor - M. Ridwan (Universitas Andalas, 2006)
The objectives of the study were to identify potency for development and possibilities for empowerment of small scale livestock product processing industries located in Bogor regency. A field survey has been conducted to collect information and data from some small scale industries which process different animal products of meat, milk, skin, bone, feather and slaughter house. Data collected included: human resources, capital, technology adapted, organization, product, marketing, government support, raw materials and market competitor. Data was analyzed by using the methods of AHP (Analytical Hierarchy Process) and Fuzzy NN – MCDM (Non Numeric Multi Criteria Decision Making). The results found that the most potency for development of small scale industry for animal product processing were the industries processing meat and milk. The most important aspect needed for empowerment was marketing.